A novel method for real-time estimation of insoluble solids and glucose concentrations during enzymatic hydrolysis of biomass. (March 2019) - Kadhum, Haider Jawad; Mahapatra, Durga Madhab; Murthy, Ganti S.
Graphical abstract: Highlights: A novel approach for real-time estimation of insoluble solids content and glucose. Cost effective model development using mixing torque for hydrolysis monitoring. 90% reduction in mixing torque during the first 12 h. Rotational speeds of 50–100 rpm for 45% solids are recommended. Fed-batch ratio of 44:22:17:17% yielded higher glucose conversions. Abstract: The study describes a novel method using instantaneous mixing torque and rotational speed to estimate insoluble solids and glucose concentrations during enzymatic hydrolysis of biomass. This method is cost-effective for real-time monitoring and control of enzymatic hydrolysis and potentially scalable. The model was developed using biomass slurries at three solids loading (20, 30 and 45%) at various rotational speeds from 50 to 400 rpm. The results showed a significant drop in mixing torque at 12 h with high solids loading. Maximum glucose concentration (205 g/l) during hydrolysis was achieved at 45% solids loading. Insoluble solids and glucose concentration as a function of torque and rotational speeds were modeled using a modified Herschell-Bulkley model. The model describes the experimental observations with high fidelity (R 2 = 0.84) and can be used for real time monitoring of many multiphase reaction systems as enzymatic hydrolysis of lignocellulosic biomass and dry grind corn ethanol processes.